Designing Team Projects for Envy-Free Group Collaboration to Overcome Free-Rider Problem - Mengyu Luo; Chaeyoung Lee; Jian Wang; Soobin Kwak; Hyundong Kim; Junseok Kim (Discrete Dynamics in Nature and Society)
We propose an envy-free team project called “color team project”. The primary motivation behind this approach is to prevent free-rider behavior and create a fair evaluation system that avoids jealousy among team members. In the team project, each team member indicates their contribution to the final team output using a color or their name. To evaluate the color team project, we use the number of pixels as the decision matrix, which includes pixels from the entire work (“All”), the methodology section (“Methodology”), the experimental section (“Results”), and the “Title”. The attribute weight is determined through steps that include standardization and information entropy. We then determine the ranking order of a team project using either the Simple Additive Weighting (SAW) method or the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method, and it is verified by the analytic hierarchy process (AHP) method. By applying the color team project, we can overcome the free-rider problem and maintain the positive aspects of team projects, such as effective communication, collaboration, and negotiation.